Pengaturan Frekuensi Inverter Satu Phasa DC/AC pada Generator Mini Portable Satu Phasa 2500 VA dengan System Line - Amir Hamzah Pohan (Universitas Muhammadiyah Tangerang, 2021)
Safe measures for frequency regulation of single-phase inverter in DC / AC building designs. This research focuses on the factors associated with safe measures for frequency regulation of single-phase inverters in DC / AC building designs. The manufacture of a single-phase portable mini generator with a line system is to make a power plant that is environmentally friendly and can be used in an easy and efficient way. The research was conducted using a design or research method by making a wiring generator set design with a line and conducting a series of tools and testing the performance of the tools. To determine the inverter capacity, we first know the capacity and number of ac motors used. Based on the results of measurements made in this study, using an inverter, it is shown that each increase in the regulated frequency results in a change in the speed of the induction motor. The results of this generator are obtained by observing the effect of frequency on rpm, torque and power Keywords: Mini generator, System line, Single phase inverter